2022
DOI: 10.3389/fmicb.2022.1031683
|View full text |Cite
|
Sign up to set email alerts
|

A sex and gender perspective for neglected zoonotic diseases

Abstract: S and Scagliarini A ( ) A sex and gender perspective for neglected zoonotic diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Due to the neglected status of leptospirosis and the broader gap in sex-disaggregated CSIDs research, limited gender-specific data hinders our understanding of infection risks and behavioural exposures in women (10,22,48,49). To address this gap, qualitative focus group discussions segregated by gender may help to shape hypotheses surrounding exposures in women, which could subsequently be measured and tested in serosurveys (50).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the neglected status of leptospirosis and the broader gap in sex-disaggregated CSIDs research, limited gender-specific data hinders our understanding of infection risks and behavioural exposures in women (10,22,48,49). To address this gap, qualitative focus group discussions segregated by gender may help to shape hypotheses surrounding exposures in women, which could subsequently be measured and tested in serosurveys (50).…”
Section: Discussionmentioning
confidence: 99%
“…While research employing a gender perspective to the study of leptospirosis remains scarce, several studies in the city of Salvador, Brazil, have suggested that behaviour may be an important determinant of the gender-specific risks associated with the disease (8,22,23). For example, a previous study used GPS to monitor residents’ mobility and found that men covered a larger area than women over a 24-hour period, as did infected male participants when compared with uninfected males (23).…”
Section: Introductionmentioning
confidence: 99%